Assessment of laser weld bead quality via acoustic emission and optical coherence tomography - Hsu, L-W; Parchegani, S; Libutti-Núñez, H H; Barros Ribeiro; K S; Moreira Bessa, W; Salminen, A (United Kingdom, 2026)
Laser welding processes are inherently dynamic, and precise monitoring can validate process stability and product quality especially when laser parameters are not optimized, potentially resulting in quality variations within a single pass. In this study, an optical microphone is employed to monitor airborne acoustic emissions (AE) generated during a bead-on-plate laser welding process on E36 grade structural steels, while optical coherence tomography (OCT) is used to measure the keyhole depth. The optical microphone measures broadband and airborne acoustic data, recording transient events within the process, such as keyhole dynamics and metal vaporisation from the melt pool. With this multi-sensor monitoring approach, the correlation between process parameters, keyhole depth and weld profile is investigated. The results have shown a positive relationship between laser power changes in both acoustic emission characteristics and keyhole depth. By comparing these datasets, we identify distinct acoustic signatures corresponding to welding modes and penetration completeness. These findings demonstrate the methodology for integration of airborne acoustic emission signature with OCT for real-time diagnostics of laser welding processes. This multi-sensor approach, when integrated into a control loop, has the potential to enhance quality assurance for various manufacturing applications.
20th Nordic Laser Materials Processing Conference